Upaya Pencegahan Gagal Ginjal Kronik Usia Dini: Efforts to Prevent Chronic Kidney Failure at an Early Age - Imamah, Nur Fithriyanti; Wahyuni, Marjan; Andriani, Dwi Astri; Sari, Romadhona Rusdi Ambar (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Chronic kidney failure is one of the diseases that is experiencing an increase in cases, including in children. This condition can lead to serious complications if not treated properly from an early age. This community service activity aims to enhance elementary school students' understanding of preventing chronic kidney failure through health education and observation of fluid consumption patterns. The methods employed consist of three stages: preparation, implementation, and evaluation. Health education was provided to 20 elementary school students in grades 5 and 6, covering topics such as kidney function, causes of kidney failure, and healthy lifestyle practices to prevent this disease. Evaluation was conducted through pre-tests and post-tests, as well as observation of fluid consumption. The study's results showed a significant increase in participants' knowledge levels, with an average pre-test score of 8.3 and a post-test score of 9.8 (p = 0.002). Additionally, the results of the observations showed variations in fluid consumption, with the majority of respondents choosing water as their main drink. This activity concludes that health education is efficacious in improving students' knowledge about preventing chronic kidney failure. It is recommended that similar activities be carried out continuously and integrated into health promotion programs in schools to increase awareness and early prevention of chronic kidney failure.